CAPTURING CURRENT RESEARCH TRENDS ON THE UTILIZATION OF CHATGPT IN SCIENCE EDUCATION - Utami, Amaira; Rusmana, Ai Nurlaelasari; Rahayu, Dita Puji (Jurnal Pendidikan Matematika dan IPA, 2025)
In this modern era, the emergence of artificial intelligence (AI) in the educational context has brought significant benefits to teachers and students. One widely used artificial intelligence type is large language models (LLMs) like ChatGPT. This study aims to capture the current research trend related to the use of ChatGPT in the context of science education. A bibliometric analysis was conducted using the Scopus database to analyze current research trends on ChatGPT and Science Education. A total of 74 documents published in 2023-2025 were collected. Rstudio, OpenRefine, VOSviewers, and Microsoft Excel were utilized to analyze the data. It is perceived that Goethe University Frankfurt, National Cheng Kung University, Technical University of Munich, and University College London are the most productive affiliations, with eight publications over the timespan. Moreover, the USA is the leading country, with 51 publications, as one of the high-yielding countries. Citation analysis was carried out to define the most impactful author. It is known that Grant Cooper from Curtin University is the most impactful author. To sum up, this study contributes to presenting current research trends related to the use of ChatGPT in science education that might provide insightful information for future research.